2022
DOI: 10.1155/2022/5248288
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Changes of Intestinal Microflora Structure in Long-Term Night Shift Nurses

Abstract: Objective. To investigate the influence of long-term night shift nurses on the composition. Methods. The feces of 30 night shift nurses (test group) and 30 day shift nurses (control group) over 1 year were collected, and double-end sequencing based on bacterial 16S rDNA V3 + V4 and fungal 18S rDNA V3 + V4 was used to determine the differences by OTU clustering, diversity, flora abundance, and differential analysis. The results of 60 samples were sequenced for a total of 3, 052. There were 418 high-quality sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%